Application of Dynamic Compaction in a Project with Smart Acceptance Criteria - Hamidi, Babak; Varaksin, Serge; Nikraz, Hamid (Research Publishing, 2012)
Al Madina A’Zarqa, is a multibillion dollar development project in Oman, and the first stage of this project covers an area of approximately 78,500 m2. The preliminary geotechnical investigation showed that the top 8 m of ground was composed of very loose to dense saturated silty sand followed by 3 m of sandy silt. This study revealed that the in-situ ground conditions would not be able to safely support the structures and that ground improvement had to be carried out to ensure the safe transfer of structural loads to the foundations. While original acceptance criteria were based on minimum cone resistance values, alternative specifications were developed that stipulated quick criteria as a first check only in the form of minimum CPT test values followed by minimum value Menard Pressuremeter Tests (PMT),and ultimately bearing capacity and finite element settlement calculations for final verification and confirmation of soil improvement acceptance. Ground improvement was performed by the dynamic compaction method with pounders weighing up to 23 tons. In all 168 CPT and 43 PMT tests were used to verify that acceptance had been achieved.